EFEKTIVITAS LARUTAN ASAM UNTUK MENURUNKAN KADAR MERKURI (Hg) PADA IKAN PATIN (pangasius pangasius) - Resna Maulia; Normila Normila (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Mercury in catfish (pangasius pangasius) indicated the pollution in the Kahayan Rivers Kalimantan Tengah and caused the negative effect for health. The prevention effort do soaking process with the acid solution like lime (citrus aurantifolia) and Limau Kuit (Citrus hystrix) solution before consumed. The aim this study was determine the effectiveness of acid solution concentration to decrease mercury level in the catfish (pangasius pangasius). The methode of this study was experimental with pre and post desaign and use 50 mg meat catfish as sampel. The soaking process use varians concentration of acid solution ware 10%, 25% and 50% for 30 minutes. The result showed that the mean of mercury level in the catfish from Kahayan River was 0, 380±0,072 and lower than maximum limit by SNI 7387 Years 2009. The effectiveness of lime (citrus aurantifolia) solution for 10%, 25% and 50% were 18,11%, 46,98% and 65,09% and the effectiveness of Limau Kuit (Citrus hystrix) for the same concentration were 46,03%, 73,28% and 27, 25%. it is concluded that the highest of effectiveness to decrease the mercury level in the catfish was 25% of limau kuit and the lowest of effectiveness was 10% of lime solution. This study was expected to give information about lime an limau kuit solution ability for reduce mercury level in catfish before consumed.